A importância da exocitose de lisossomos durante a invasão de células deficientes em LAMP por amastigotas extracelulares de Trypanosoma cruzi - Gaspar, Emanuelle Baldo [UNIFESP] (2009)
In the present work the role of LAMP-1 and LAMP-2 in invasion by extracellular amastigotes of T. cruzi was evaluated. Murine embryonic fibroblast (MEF) knockout for one or both proteins were used. Three different pairs of wild type/double knockout cells were used, besides one single LAMP-1 or LAMP-2 knockouts cell lineage. Extracellular amastigotes invasion rate was higher for two of the double knockout clones but not for the other one. When compared to their respective wild type clones, the extracellular amastigotes showed higher infectivity in LAMP-2 knockouts, but no difference was seen in LAMP-1 knockout cells. In addition, HeLa and two wild type lineages of MEFs were submitted to siRNA treatment. Although the siRNA treatment was efficient, since down regulation in protein expression was observed, there was no difference in amastigotes cell invasion in cells treated in comparison to the controls. These results indicated that LAMP proteins were not important to extracellular amastigotes cell invasion. To explain the reason for a higher invasion rate observed in some cells, lysosomal exocytosis was evaluated. Fortunately, higher lysosomal exocytosis correlated with a higher invasion rate. Moreover, it was performed a CD63/LIMP-2 acquisition kinetics and the same cells that showed higher invasion rate, presented higher lysosomal marker acquisition in early invasion times. Taken together, these findings suggest that lysosomal exocytosis was important to amastigotes cell invasion. Lysosomal marker acquisition kinetics (LAMP-1 here) were performed also in HeLa and Vero cells. Once again lysosome exocytosis was important to extracellular amastigotes cell invasion. Finally, previous results with the same MEFs used in this study demonstrated that LAMP proteins were essential to phagosome-lysosome fusion. Here, it was demonstrated that in knockout cells parasitophorous vacuoles are clearly CD63/LIMP-1 stained, indicating that in MEFs, extracellular amastigotes enter cells by a mechanism other than receptor-mediated phagocytosis.